Valuing Supporting Soil Ecosystem Services in Agriculture: A Natural Capital Approach. (1st September 2015) - Brady, Mark V.; Hedlund, Katarina; Cong, Rong‐Gang; Hemerik, Lia; Hotes, Stefan; Machado, Stephen; Mattsson, Lennart; Schulz, Elke; Thomsen, Ingrid K.
Abstract : Soil biodiversity through its delivery of ecosystem functions and attendant supporting ecosystem services—benefits soil organisms generate for farmers—underpins agricultural production. Yet lack of practical methods to value the long‐term effects of current farming practices results, inevitably, in short‐sighted management decisions. We present a method for valuing changes in supporting soil ecosystem services and associated soil natural capital—the value of the stock of soil organisms—in agriculture, based on resultant changes in future farm income streams. We assume that a relative change in soil organic C (SOC) concentration is correlated with changes in soil biodiversity and the generation of supporting ecosystem services. To quantify the effects of changes in supporting services on agricultural productivity, we fitted production functions to data from long‐term field experiments in Europe and the United States. The different agricultural treatments at each site resulted in significant changes in SOC concentrations with time. Declines in associated services are shown to reduce both maximum yield and fertilizer‐use efficiency in the future. The average depreciation of soil natural capital, for a 1% relative reduction in SOC concentration, was 144 € ha −1 (SD 47 € ha −1 ) when discounting future values to their current value at 3%; the variation was explained by site‐specific factors and the current SOC concentration. Moreover, the results show that soil ecosystem services cannot be fully replaced by purchased inputs; they are imperfect substitutes. We anticipate that our results will both encourage and make it possible to include the value of soil natural capital in decisions.